Transactional Sex among Noninjecting Illicit Drug Users: Implications for HIV Transmission - Rafael Alves Guimarães; Aurélio Goulart Rodovalho; Inaina Lara Fernandes; Graciele Cristina Silva; Rodrigo Lopes de Felipe; Ivânia Vera; Valéria Duarte Gregório; Roselma Lucchese (The Scientific World Journal)
Noninjecting illicit drug users (NIDUs) present high risk for HIV infection, due especially to transactional sex. This study aimed to estimate the prevalence and risk factors for transactional sex among NIDUs in the Southwest region of Goiás State, Central Brazil. The prevalence of self-reported transactional sex was 22.8%. Prevalence in women and men was 52.7% and 16.8%, respectively, a significant difference (p<0.001). Crack use and history of sexually transmitted infections (STI) were risk factors for transactional sex in men. Homelessness, crack use, sex under the influence of drugs, and history of sexual violence were risk factors for transactional sex in women. A high prevalence of transactional sex was observed among NIDUs. This risk behavior may contribute to the high rates of HIV among this population and their social networks and in the general population.